2023
DOI: 10.22454/primer.2023.253936
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening Decisions From Student-Led Telemedicine Initiative During COVID-19

Abstract: Background and Objectives: With the onset of the COVID-19 pandemic, there has been a significant decrease in colorectal cancer (CRC) screening leading to delayed diagnoses and increased cancer deaths. To mitigate these burgeoning gaps in care, we developed a medical student-led service learning project aimed at improving rates of colorectal cancer screening at the Farrell Health Center (FHC), a primary care practice within the Ambulatory Care Network (ACN) at New York-Presbyterian Hospital. Methods: A cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In addition to focusing on health promotion, the included studies showed that student-led interventions improved screening and the early detection of chronic conditions. The role of students in screening services is not new; there is a vast amount of literature showing that medical students can use screening services to increase the early detection of diseases, such as hypertension, diabetes, and cancer (2, 30-32). However, the unique focus of our findings is that public health students in particular – upon receiving adequate training or supervision – can also engage in these types of activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to focusing on health promotion, the included studies showed that student-led interventions improved screening and the early detection of chronic conditions. The role of students in screening services is not new; there is a vast amount of literature showing that medical students can use screening services to increase the early detection of diseases, such as hypertension, diabetes, and cancer (2, 30-32). However, the unique focus of our findings is that public health students in particular – upon receiving adequate training or supervision – can also engage in these types of activities.…”
Section: Discussionmentioning
confidence: 99%